ANALISIS PERILAKU FITNAH DITINJAU DARI PERSFEKTIF TEOLOGI KRISTEN - Illu, Jonidius; Gulo, Eliyunus; Nome, Nehemia; Rosdiana, Merry Wati (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2025)
Abstract. The main issues addressed in this article are: first, the frequent occurrence of slander among Christians without considering their identity as Christians; second, slander is often seen as a normal action because it is perceived as a form of revenge; third, slander is carried out without rationally considering its impact; fourth, slander is done with the motivation of gaining personal benefit. The author aims to provide an analysis of slanderous behavior from a Christian theological perspective so that Christians do not easily fall into the trap of engaging in or being influenced by slander. Additionally, Christians should not be quick to believe in rumors, but instead, should critically analyze their validity with concrete evidence. The research method used is qualitative. In conclusion, slanderous behavior does not reflect the true identity of a Christian. Keywords: Slanderous Behavior, Christian theology